UMP triz innovation exposition 2.0 - Haslinda, Hashim; Wan Suraya, Wan Nik (2018)
Pekan, 13 May- It was an unforgettable day for all Soft Skills II students as they had the chance to participate in UMP TRIZ Innovation Exposition 2.0 for the year 2018 at the Astaka Hall, UMP Gambang Campus. After 13 weeks of thorough, grueling and detailed discussions during academic lectures in the classroom, only 95 groups were selected from 181 groups (570 students) from a total of 1089 students enrolled in Soft Skills II course for this semester.